OXIDATIVE STRESS AND ROLE OF ANTIOXIDANTS IN MALE INFERTILITY - Choudhary, Raghuveer; VK, Chawala; ND, Soni; Kumar, Jayant; RK, Vyas (Pakistan Journal of Physiology, 2010)
With regular cohabitation without any protection if women do not conceive for at least a period of one year is labelled as infertility. It is based on the observation that most of the normal couples achieve conception within a year of initiation of regular sex. Infertility affects approximately 15% of all couples trying to conceive. It’s a major clinical problem, affecting people medically and psychologically. Male factor infertility is the major cause in roughly half of the cases, and no identifiable cause can be found in over 25% of infertile males. Out of many causes of male infertility Oxidative stress (OS) has been attributed to affect the fertility status and thus, it has been studied extensively in recent years. Excessive production of free radicals or reactive oxygen species (ROS) can damage sperm and ROS has been extensively studied as one of the major mechanism of infertility